KONSENTRASI TRIIODOTIRONIN (T3) PADA CAIRAN FOLIKEL YANG DIISOLASI DARI FOLIKEL SAPI POTONG YANG BERASAL DARI RPH GIWANGAN YOGYAKARTA - , MITHA DEWI RATNASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The T3 hormone have an effect on every body's physiological processes, including growth, development, metabolism, and reproduction. This study was conducted to determine concentration of T3 on large and small ovarian fluid follicles, which it can be assesment of productivity of cows. In this study used nine small follicles and nine large follicles. The follicles taken from cattle that have been slaughtered in the abattoir Giwangan Yogyakarta later cleared. Follicular fluid were taken using a syringe and then placed in a microtube. The examination performed by method ELISA kits commertial. Data were analyzed using one-way Analysis of Variant (ANOVA). The result this study, the average concentration of triiodothyronine (T3) follicular fluid from small and large follicle were 1,51 Â± 0,339 ng/mL and 2,34463 Â± 0,463 ng/mL respectially. Analysis statistical showed that are different significant (P<0,05) the concentration T3 of liquor folliculi small follicle and large follicle. The conclusion of this study is the bigger of ovaryâs diameter, then concentration of triiodothyronine (T3) is higher, increasing of T3 hormone will increase the concentration of estrogen and progesteron which it means that cows has good productivity. Key words: beef cattle, follicular fluid, triiodothyronine, ELISA